Imaginary, form and expression: fashion window display and the intertwining between consumption, style and sensitiveness (ModaPalavra e-periódico, 2024)
The study aims to understand the mechanisms through which shop windows affect us and establish dialogues with our stylizing dimension. The shop window is a poetic device present in urban life which is capable of catalyzing our emotions toward consumption and the fulfillment of our desires. Firstly the article shows the sensitive or perceptive experience of the spectator and the reconfigurations of narrativity. Then we highlight the window display as an emancipated unit with its world, capable of maintaining a dialogical relationship with the spectators and the sociabilities. Afterward, we mark the artistic dimension present in the atmosphere of consumer culture and style. On this basic, exploratory, and qualitative  research , we rely on an aesthetic and phenomenological approach  conceptually. The contributions of Paul Ricoeur (1986); Maurice Merleau-Ponty (1994); Georg Simmel (2016;2009;2013), and Walter Benjamin (2009) are the base of our methodological and conceptual guide. As a result, it highlights the way in which the dynamics that are present in the aesthetic experience are woven into the flows of sociability, whose intertwining appears to be inseparable between emotions, consumption, communicability, history and culture.
Keywords: window display; sensitiveness; consumption